(untitled) (Ocean and Coastal Research, 2022)
A scientific cruise between November 15 and December 18, 2019 aboard R/V Vital de Oliveira collected offshore seawater samples at 59 stations between the states of Ceará and Bahia. The objective was to identify hydrocarbon levels potentially associated with the mysterious oil spill that reached the northeastern coast of Brazil. Median concentrations of aliphatic hydrocarbons (AHs, 0.79 µg L-1) and polycyclic aromatic hydrocarbons (PAHs, 5.39 ng L-1) do not indicate contamination by crude oil and are comparable to baseline levels previously found in other areas of the Brazilian continental margin. The detailed composition of both groups of hydrocarbons revealed that some samples were contaminated during sampling and/or handling on-board. The data set presented herein highlights the difficulty in tracking small oil patches spread over a huge ocean area and, more importantly, the need for improving protocols of national research vessels used to collect seawater samples for trace organic analyses.